Medical pharmacology and therapeutics - Waller, Derek G.; Hillier, Keith , 1943-; Renwick, Andrew G. (Saunders Elsevier, 2010)
This textbook on medical pharmacology and therapeutics provides a basis for learning about a safe and effective prescribing of modern medicines by including descriptions of the pathogenic mechanisms of the disease and where and how drugs have their actions and unwanted effects